MicroRNAs in acute kidney injury. Issue 1 (December 2016) - Fan, Pei-Chun; Chen, Chia-Chun; Chen, Yung-Chang; Chang, Yu-Sun; Chu, Pao-Hsien
Abstract Acute kidney injury (AKI) is an important clinical issue that is associated with significant morbidity and mortality. Despite research advances over the past decades, the complex pathophysiology of AKI is not fully understood. The regulatory mechanisms underlying post-AKI repair and fibrosis have not been clarified either. Furthermore, there is no definitively effective treatment for AKI. MicroRNAs (miRNAs) are endogenous single-stranded noncoding RNAs of 19~23 nucleotides that have been shown to be crucial to the post-transcriptional regulation of various cellular biological functions, including proliferation, differentiation, metabolism, and apoptosis. In addition to being fundamental to normal development and physiology, miRNAs also play important roles in various human diseases. In AKI, some miRNAs appear to act pathogenically by promoting inflammation, apoptosis, and fibrosis, while others may act protectively by exerting anti-inflammatory, anti-apoptotic, anti-fibrotic, and pro-angiogenic effects. Thus, miRNAs have not only emerged as novel biomarkers for AKI; they also hold promise to be potential therapeutic targets.